Crosstalk between Epigenetics and Autophagy in Metabolic Dysfunction-Associated Steatotic Liver Disease - Irfana Zahoor; Gh Jeelani Mir; Nazir Ahmad Lone; Nissar Ul Ashraf (Journal of Obesity & Metabolic Syndrome)
Metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as non-alcoholic fatty liver disease, is one of the most common causes of liver dysfunction worldwide, posing a significant economic burden. However, our understanding of the cellular and molecular mechanisms underlying the pathogenesis of MASLD is in its early stages. Over the last two decades, epigenetic mechanisms and autophagy have emerged as two independent phenomena that control cellular and molecular processes in health and disease. Epigenetic events and defects in autophagy have been linked with the pathogenesis of MASLD and metabolic dysfunction-associated steatohepatitis (MASH) in cellular studies, mouse models, and human research. However, the connection between epigenetic mechanisms and autophagy regulation in MASLD and MASH pathogenesis remains unclear. This review highlights the importance of epigenetic modifications and their regulatory switches in controlling downstream pathways that significantly impact metabolic disease pathogenesis. We also review the need to identify key epigenetic factors regulating autophagy in MASLD and MASH pathogenesis. Such insights could aid the development of novel strategies to restore autophagy and improve disease outcomes.